Age and Psychological Well-being as Predictors of Male Child Parenting among Married Adults - Ramata Funsho Sanni; Adekola Kamil Lasisi; Taiye Hassan Ahmed (Suluh: Jurnal Bimbingan dan Konseling, 2024)
Age is a critical factor in parenting, as parenting styles and attitudes can vary significantly across different age groups. Psychological well-being encompasses an individual's emotional health, life satisfaction, and overall mental state. The study examined age and psychological well-being as predictors of Male Child Parenting among married adults in Kwara State. A descriptive survey was used. The study was conducted on 384 married adults in Kwara Central Senatorial District, Kwara State, using a self-designed questionnaire called "Age and Psychological Wellbeing as Predictors of Male Child Parenting Questionnaire (APWDMCPQ). The questionnaire was validated by experts and its reliability was established through pilot testing using the Split-half method. The results were correlated using Spearman-Brown Correlation Coefficient Statistics (PBCCS) with a reliability index of 0.76. The study used mean and standard deviation to present answers to research questions, and Analysis of Variance (ANOVA) statistics to test hypotheses at a 0.05 level of significance. The study show that there is a significant effect of age on male child parenting (F.cal.=25.60, p.<0.05). The study found that there is no significant effect of psychological well-being on male child parenting (F.cal.=3.34, p.>0.05). The study found that age significantly impacts male-child parenting, but parental psychological well-being doesn't significantly affect it. It recommended that married adults aged 25-35 and 36-45 should seek counselling to develop appropriate parenting skills. Additionally, they should be educated on coping mechanisms to withstand the pressure of parenting male children, improving their psychological well-being and enabling effective male child parenting.